Adesão de idosos a programa de atividade física em unidade de atenção primária à saúde - Monteiro, Maira Cury [UNESP] (2014)
The current epidemiological scenario confirms the transition patterns of occurrences of diseases in recent decades, a change called epidemiological transition, characterized by decreased occurrence of infectious-contagious diseases and higher chronic non-communicable diseases (NTCDs). In Brazil, they represent about 72% of all deaths in the country. Physical inactivity, together with other behavioral factors, such as the use of tobacco and dietary profile, are responsible for about 80% of the total burden of major chronic diseases. Considering that the Brazilian Centralized Health System (Sistema Único de Saúde) has encompassed and implemented physical activity programs in primary healthcare units, and considering the low adherence of elderly people to these programs, the purpose of this study is to capture from the experience of elderly people the factors that condition their adherence to and dropout from oriented physical activity in the Family Health Strategy. Qualitative research, using forms and non-conducive interview, administered to two groups of individuals: adherence group (AG) and dropout group (DG), with analysis methodology through analysis of thematic type of contents. The results show that elderly people's adherence to or dropout from physical activity programs in primary healthcare units originate from a series of multifactoria aspects as pleasant feeling to the realization exercise, improve health conditions, compliance with recommendations of professionals in health and social life and aspects that stimulate the dropout is sorrow in exercise tolerance, worsening health condition, compliance with contraindication for health professionals, prioritize other daily life activities, negative perception of the conditions of infrastructure related to exercise and fitness difference between program participants. Recommend actions to minimize the withdrawal of the elderly from physical exercise in primary care settings ...